Analisis Faktor-faktor yang Berpengaruh terhadap Pelaporan Keuangan [Studi Empirik di BEI Periode 2014-2016] - Mario Kristop Jaori, Mulyani (Jurnal Akuntansi, 2018)
Timeliness is the availability of information to the decision maker when needed before the information loses power to influence the decision. If there is an unnecessary delay in financial reporting, the financial statements will lose their relevance. The purpose of this research is to know the empirical evidence of the influence of Profitability, Solvability, Company Size, Firm Size, and Age of Company to the timeliness of financial reporting to property and real estate companies listed on Indonesia Stock Exchange (BEI) in 2014-2016. This research uses logistic regression analysis method. The data used are secondary data taken through observation techniques. The sampling technique used is non probability, that is purposive sampling method. The result of logistic regression shows that profitability, solvability, and firm size have significant effect to timeliness. While the firm size and age of the company has no significant effect on timelinessThis study resulted in the conclusion that There is sufficient evidence of profitability (ROA) have a significant positive effect on timeliness. The result of Solvability (DER) and the Company's size on timeliness can not be concluded. There is not enough evidence of Firm Size has significant effect on timeliness. And, There is not enough evidence Company Age has significant effect on timeliness.Keywords : Timeliness, Profitability, Solvability, Company Size, Firm Size, Company Age